An evaluation of the budget impact of a new 20% subcutaneous immunoglobulin (Ig20Gly) for the management of primary immunodeficiency diseases in Switzerland - Pollock RF; Meckley LM (Dove Medical Press, 2018)
Richard F Pollock,1 Lisa M Meckley2 1Ossian Health Economics and Communications GmbH, Health Economics and Outcomes Research, Basel, Switzerland; 2Shire Plc, Outcomes Research and Epidemiology, Cambridge, MA, USA Introduction: While most individual primary immunodeficiency diseases (PID) are rare, the collective prevalence of PID results in a substantial economic and clinical burden. The aim of this study was to evaluate the budgetary implications of Ig20Gly (Immune Globulin Subcutaneous [human] 20% solution; CUVITRU®, Baxalta US Inc, now part of Shire Plc, Westlake Village, CA, USA) as a treatment for PID relative to intravenous immunoglobulin (IVIG) and other subcutaneous immunoglobulin (SCIG) formulations in the Swiss health care setting.Materials and methods: A budget impact model was developed in Microsoft Excel to capture the estimated prevalence of PID in Switzerland, the proportion of patients treated in different health care settings, and the costs of administering SCIG and IVIG in each setting. Unit costs were based on a recent cost-minimization analysis of SCIG in Lausanne, and drug costs were taken from the Spezialitätenliste. All costs were reported in 2016 Swiss Francs (CHF), and future costs were not discounted.Results: The total cost of treating PID in Switzerland was estimated to be CHF 11.16 m over 3 years, comprising CHF 9.28 m of drug costs and CHF 1.87 m of ancillary costs, including health care professional time and other administration costs, such as pumps and needle sets. The analysis showed that using Ig20Gly in place of other SCIG formulations would be cost neutral, while using Ig20Gly in place of IVIG would result in savings of 4.0%.Conclusion: Ig20Gly would be cost neutral relative to existing SCIG products and would result in cost savings relative to IVIG in patients with PID in Switzerland, even with modest uptake. Keywords: costs and cost analysis, immune system diseases, immunoglobulin, Switzerland